2021
DOI: 10.3390/nu13062032
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota Profile and Its Association with Clinical Variables and Dietary Intake in Overweight/Obese and Lean Subjects: A Cross-Sectional Study

Abstract: We aimed to differentiate gut microbiota composition of overweight/obese and lean subjects and to determine its association with clinical variables and dietary intake. A cross-sectional study was performed with 96 overweight/obese subjects and 32 lean subjects. Anthropometric parameters were positively associated with Collinsella aerofaciens, Dorea formicigenerans and Dorea longicatena, which had higher abundance the overweight/obese subjects. Moreover, different genera of Lachnospiraceae were negatively assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
55
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(75 citation statements)
references
References 37 publications
7
55
2
1
Order By: Relevance
“…A 2020 study reported a positive association between Acidaminococcus and body mass index (BMI), as well as waist and hip circumferences in Bangladeshi adults [ 70 ]. Companys et al demonstrated that anthropometric parameters were positively associated with Collinsella aerofaciens , Dorea formicigenerans and Dorea longicatena , which had higher abundances in overweight/obese subjects [ 71 ]. Saturated fatty acids were negatively associated with the Intestinimonas , a biomarker of the overweight/obese subjects.…”
Section: Gut Microbiota Composition In Cardiovascular Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…A 2020 study reported a positive association between Acidaminococcus and body mass index (BMI), as well as waist and hip circumferences in Bangladeshi adults [ 70 ]. Companys et al demonstrated that anthropometric parameters were positively associated with Collinsella aerofaciens , Dorea formicigenerans and Dorea longicatena , which had higher abundances in overweight/obese subjects [ 71 ]. Saturated fatty acids were negatively associated with the Intestinimonas , a biomarker of the overweight/obese subjects.…”
Section: Gut Microbiota Composition In Cardiovascular Diseasementioning
confidence: 99%
“…The authors reported that the microbiome had little effect on LDL-C or total cholesterol (TC). A more recent 2021 study showed that genera of the Lachnospiraceae family are negatively associated with lipid CVD risk factors including body fat, LDL-C and TC [ 71 ]. Liang et al demonstrated that a high-fat and high-cholesterol diet (HFHCD) significantly decreased the alpha diversity of the gut microbiota in mice compared with high-fat diet (HFD) alone [ 76 ].…”
Section: Gut Microbiota Composition In Cardiovascular Diseasementioning
confidence: 99%
“…Several of the reviewed studies reported a decrease in abundance of species Dorea longicatena in patients with an RTI compared to controls [ 30 , 46 , 49 , 50 , 53 ]. D. longicatena has been reported as a biomarker for obesity [ 64 ], yet it’s role in RTI is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, bacteria of the Oscillospira genus and Coriobacteriaceae family were associated with good metabolic health. In a study population encompassing people with normal weight and overweight/obesity, the abundance of specific genera correlated with metabolic characteristics 50. Notably, anthropometric parameters were positively associated with Collinsella aerofaciens , Dorea formicigenerans and D. longicatena , which had higher abundance in people with overweight/obesity.…”
Section: Gut Microbiome and Host Metabolic Phenotypementioning
confidence: 95%
“…Furthermore, a high intake of mainly saturated fatty acids (SFAs) has been associated with a decrease in gut microbial richness and diversity in both adults and infants 146 147. In people with overweight and obesity, SFAs were negatively associated with the genus Intestinimonas , whereas SFAs were positively associated with Roseburia , which was also highly abundant in individuals with normal body weight 50. In this study, habitual SFA intake exhibited opposite association profiles with butyrate-producing bacteria, depending on the BMI.…”
Section: Dietary Macronutrients Microbial Composition and Metabolic H...mentioning
confidence: 99%